2018
DOI: 10.3389/fnhum.2018.00483
|View full text |Cite
|
Sign up to set email alerts
|

Altered Sensory Insular Connectivity in Chronic Postsurgical Pain Patients

Abstract: Chronic postsurgical pain (CPSP) occurs in up to 50% of individuals after surgeries and 32% after hysterectomy, leading to major adverse effects on quality of life and socioeconomic burden. Little is known about whether and how large-scale neural networks being affected in CPSP, particularly with regard to the functional connectivity (FC) of insula which is known to be the hub of the intrinsic neural network playing a critical role in pain processing. Here, we sought to examine the dynamics of insular FC in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Our study examined aINS neurotransmitter levels in women with IBS, a mechanism that might contribute to aberrant insular function consistently observed in chronic visceral pain disorders. 3,7,9,19,32,38,50 We observed decreased concentrations of the excitatory neurotransmitter Glx in bilateral aINS in women with IBS compared with healthy women, whereas no significant group differences were found in aINS GABA+ concentrations. Furthermore, we demonstrated that longer duration of pain predicted lower Glx concentrations in the right aINS while lower Glx concentrations in the left aINS were predicted by less use of adaptive pain-coping strategies.…”
Section: Discussionmentioning
confidence: 51%
“…Our study examined aINS neurotransmitter levels in women with IBS, a mechanism that might contribute to aberrant insular function consistently observed in chronic visceral pain disorders. 3,7,9,19,32,38,50 We observed decreased concentrations of the excitatory neurotransmitter Glx in bilateral aINS in women with IBS compared with healthy women, whereas no significant group differences were found in aINS GABA+ concentrations. Furthermore, we demonstrated that longer duration of pain predicted lower Glx concentrations in the right aINS while lower Glx concentrations in the left aINS were predicted by less use of adaptive pain-coping strategies.…”
Section: Discussionmentioning
confidence: 51%
“…It has been confirmed that the insula is the nerve network hub of pain signal transmission. A clinical study has also suggested that chronic neuralgia is associated with fluctuations in the functional network and the activation of excitatory neurons in the insula [49,50]. As we knew, the dorsal posterior insula is one region that is consistently active at a high level during pain, as seen during functional brain imaging.…”
Section: Discussionmentioning
confidence: 92%
“…Patients with classical trigeminal neuralgia (CTN) had symptoms characterized by orbital pain, decreased corneal reflex and decreased vision ( 34 ). Individuals with chronic post-hysterectomy pain had decreased FC between the left sensorimotor insula and the right angular and middle occipital gyri (MOG), as well as between the left chemosensory insula, the bilateral angular gyri and the MOG following pain stimulation ( 37 ).…”
Section: Discussionmentioning
confidence: 99%